Downregulation of RWA genes in hybrid aspen affects xylan acetylation and wood saccharification. Issue 4 (3rd March 2017) - Pawar, Prashant Mohan‐Anupama; Ratke, Christine; Balasubramanian, Vimal K.; Chong, Sun‐Li; Gandla, Madhavi Latha; Adriasola, Mathilda; Sparrman, Tobias; Hedenström, Mattias; Szwaj, Klaudia; Derba‐Maceluch, Marta; Gaertner, Cyril; Mouille, Gregory; et al.
Summary: High acetylation of angiosperm wood hinders its conversion to sugars by glycoside hydrolases, subsequent ethanol fermentation and (hence) its use for biofuel production. We studied the REDUCED WALL ACETYLATION ( RWA ) gene family of the hardwood model Populus to evaluate its potential for improving saccharification. The family has two clades, AB and CD, containing two genes each. All four genes are expressed in developing wood but only RWA‐A and ‐B are activated by master switches of the secondary cell wall Pt NST1 and Pt MYB21. Histochemical analysis of promoter::GUS lines in hybrid aspen ( Populus tremula × tremuloides ) showed activation of RWA‐A and ‐B promoters in the secondary wall formation zone, while RWA‐C and ‐D promoter activity was diffuse. Ectopic downregulation of either clade reduced wood xylan and xyloglucan acetylation. Suppressing both clades simultaneously using the wood‐specific promoter reduced wood acetylation by 25% and decreased acetylation at position 2 of Xyl p in the dimethyl sulfoxide‐extracted xylan. This did not affect plant growth but decreased xylose and increased glucose contents in the noncellulosic monosaccharide fraction, and increased glucose and xylose yields of wood enzymatic hydrolysis without pretreatment. Both RWA clades regulate wood xylan acetylation in aspen and are promising targets to improve wood saccharification.